2019
DOI: 10.3847/1538-3881/ab1e52
|View full text |Cite
|
Sign up to set email alerts
|

Optical Transient Object Classification in Wide-field Small Aperture Telescopes with a Neural Network

Abstract: Wide field small aperture telescopes are working horses for fast sky surveying. Transient discovery is one of their main tasks. Classification of candidate transient images between real sources and artifacts with high accuracy is an important step for transient discovery. In this paper, we propose two transient classification methods based on neural networks. The first method uses the convolutional neural network without pooling layers to classify transient images with low sampling rate. The second method assu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The result is shown in Table 5, and it is observed that the proposed method has a better detection performance than that of the MHT and EAOM methods. Jia et al [52] proposed a method that uses a neural network for optical transient object classification. This method can reach an accuracy of 97.20% in streak-like objects with minimal SN R = 3.10.…”
Section: Detection Performance Of Space Debris In Optical Image Sequencesmentioning
confidence: 99%
“…The result is shown in Table 5, and it is observed that the proposed method has a better detection performance than that of the MHT and EAOM methods. Jia et al [52] proposed a method that uses a neural network for optical transient object classification. This method can reach an accuracy of 97.20% in streak-like objects with minimal SN R = 3.10.…”
Section: Detection Performance Of Space Debris In Optical Image Sequencesmentioning
confidence: 99%
“…In recent years, different machine learning based astronomical image classification algorithms have been developed and they have achieved higher and higher classification accuracy and recall rate (Romano et al 2006;Tachibana and Miller 2018;Gonzalez et al 2018;Burke et al 2019;Duev et al 2019a,b;Turpin et al 2020). For WFSATs, we have also proposed a transient classification method based on ensemble learning and neural networks (Jia et al 2019). Our method can achieve acceptable classification performance for different kinds of astronomical targets.…”
mentioning
confidence: 95%
“…These algorithms are also imported into data processing frameworks for WFSATs. Machine learning based image classification algorithms (Jia et al 2019;Turpin et al 2020) are integrated with classical astronomical target detection algorithms, such as: SExtractor (Bertin & Arnouts 1996) or simplexy in Astrometry (Lang et al 2010), to detect and classify astronomical targets of different kinds. For these integrated astronomical target detection frameworks, classical detection algorithms will firstly obtain positions of astronomical target candidates.…”
Section: Introductionmentioning
confidence: 99%